Benchmarking, Estimation & Productivity Assessment Framework for IT Implementation - Jha, Chandan Kumar (Indian Journal of Computer Science, 2016)
The dependence and fusion of Information Technology in modern organizations has led to the development of extremely mature service delivery models in recent years. Business units are augmenting their IT budget/spending to encapsulate & leverage the latest technology innovations thus empowering their product/service portfolio. Subsequently, technology sector is witnessing wide variance in service offerrings of IT firms offering a bouquet of solutions to meet business requirements. This beckons the need of a robust ’benchmarking and estimation’ framework for analyzing the efficacy of vendor solution and accomplish savings in the procurement phase leading to enhanced operational efficiency. Further, a proficient logical model is also needed to measure the productivity of the IT vendor vis-Ã -vis Industry standards at the end of implementation. In this paper, we would discuss the intricacies of the procurement phase and devise a reformed benchmarking, estimation & productivity assessment framework for IT Implementations.